The Routledge handbook of ideology and international relations
1 online resource.
Keywords: "The Routledge Handbook of Ideology and International Relations reviews, consolidates, and advances the study of ideology in international politics. The volume unifies fragmented scholarship on ideology's impact on international relations into a wide-ranging and go-to volume. Declarations of the 'end of ideology' have once again been proven premature: nationalisms of various stripes are thriving; ideological polarization and conflicts both within and among states are growing; and environmentalist, feminist and anti-globalization activists are intensifying their demands on international institutions and states. This timely volume presents ideology as a way of explaining these major developments of world politics, rejecting the simplistic association of ideology with passionate convictions in favor of more complex theories of ideology's influence. The chapters summarize cutting edge knowledge on major topics, suggest key implications for broader theoretical debates and frameworks, and point the way forwards to future avenues of inquiry. Contributors adopt puzzle-orientated causal, constitutive and/or critical approaches with a central focus on the determinants and effects of ideological phenomena and their interaction with other aspects of politics. This handbook is of key interest to students and scholars of ideologies, international relations, foreign policy analysis, political science, political theory and more broadly to sociology, psychology, and history. The Routledge Handbook of Ideology and International Relations is part of the mini-series Europe in the World Handbooks examining EU-regional relations"--